Pengaruh Profitabilitas Terhadap Struktur Modal Pada Perusahaan Bidang Pertanian Yang Terdaftar Di BEI - Endang Susilowati (Universitas Mitra Indonesia, 2020)
AbstractInfluence of profitability and capital structure of firm size in agriculture company listed on the indonesia stock exchange (idx), used all ratio profitabilitasn, are: Gross Profit Margin, Net Profit Margin, Return On Asset, Return On equity, Return On invesment, and Earning pershare. The purpose of this study is to determine whether these ratio profitabilitasn affect capital structure of firm size in agriculture company listed on the indonesia stock exchange (IDX). There search sample was determined by the method of purposive sampling based on the criteria company, in order to obtain a sample 4 companies.with multiple linier regression test, F test and R2 test with error limit 5%=0,05. This results of this study showed multiple regressions Y=5,005 – 114X1 – 0,22X2 + 17X3 – 0,41X4 – 0,41X5 - 0,03X6. The results of research obtained correlation coeffecient value (R) equal to (696). Coeffecient of determination R2 is (485). This means that independent variables explain Gross Profit Margin, Net Profit margin, Return On equity, Return on asset, Return on Invesment, Earning pershare impact on capital structure of 48,5% the remaining 51,5% influenced by other factors. Based on the results of F test with Fcount value of 2,024 then it can be Gross Profit Margin have positive significant impact on the capital structure. Net profit margin have a positive significant impact on capital structure, Return On Equity have positive significant impact on capital structure. Return On asset have positive significant impact on capital structure. Return On Invesment have positive significant impact on capital structure and Earning Per Share not have positive significant impact on capital structure.Keyword :Profitability, Capital Structure.